Forecasting Financial Distress of Airline Company: The Impact of Financal Performance - Desiana Rachmawati; Adipura Danang Maulana (Journal of International Conference Proceedings, 2022)
This study aims to predict the financial distress of airline companies which is influenced by the ratio of liquidity, solvency, profitability, activity and investment. This research is inferential research with a quantitative approach. This research used financial statements of airline companies listed on the Indonesia Stock Exchange in 2018-2021 as the data. Data analysis was performed using multiple linear regression. The results showed that the liquidity ratio (Current Ratio) and solvency ratio (Debt to Equity Ratio) partially had no effect on the prediction of financial distress as measured using Springate model. Profitability ratio (Return on Assets), activity ratio (Total Assets Turnover) and investment ratio (Price Erning Ratio) partially have a positive effect on the prediction of financial distress. The profitability ratio has an influence of 81%, the activity ratio has 27.8% and the investment ratio has 7.6% on the prediction of financial distress. The prediction result of financial distress are not solely influenced by the company's ability to pay debts, both short term and long term. Conditions related to asset performance, such as Return on Assets and Total Asset Turnover actually affect the prediction results of financial distress.